To flee or not to flee: Responses to persecution and the issue of relocation - Sauer, Christof (Missionalia: Southern African Journal of Missiology, 2013)
Religious persecution of believers contributes to migration and relocation. Three alternative responses to persecution or the threat of persecution can be discerned in Scripture: Avoiding, resisting, and enduring for those affected, and mandatory solidarity for the rest of the body of Christ. Advocacy and mission agencies are faced with the question whether relocation of persecuted believers is a viable option and provides a long-term holistic solution. The results of the discussion of a working group on the issues faced by Christian believers of Muslim background in the Middle East on the pros and cons of relocation within a country, within a region, outside a region are presented.